Needs Assessment Kompetensi Pelengkap Mahasiswa Pendidikan Islam Anak Usia Dini Berdasarkan Kebutuhan Pengguna - Fitriah, Nurlaeli (Indonesian Journal of Islamic Early Childhood Education, 2017)
The purpose of this study is to identifying competences of students of Department of Pendidikan Guru Raudhatul Athfal in Tarbiyah and Teaching Faculty UIN Maulana Malik Ibrahim Malang that needed by users. This study using needs assessment approach for finding competences of student that needed by users. This study used a quantitative approach and the type of this study was a survey research (quantitative descriptive). Data was collected by using questionnaires and interviews. The result of this study are competences that need to be owned by the students based on priority needs. They are as follows: (1) Factor 1 consist of skills related to the skills intra-personal namely control emotions, affection, self confidence, work hardly, motivation, discipline, never surrender, diligent, initiative, creativity, adaptability, ability of IT, (2) Factor 2 consist of skills related to the skills of interpersonal namely the ability of Arabic, teamwork, ability 0f english, proficiency, leading a team, written communication, public speaking, verbal communication; (3) Factor 3 consists of skill related to technical skill that are praktik ibadah, hafalan surat pendek, skill of arts, baca tulis al-Qur?an, skill of music, skill of dancing, doa-doa harian.